Long term outcome of treatment of end stage renal failure. Issue 1 (January 1988) - Henning, P; Tomlinson, L; Rigden, S P; Haycock, G B; Chantler, C
Abstract : The most common causes of end stage renal failure in 46 children (mean age 11 years, range 4-14) treated between January 1972 and June 1977 were: reflux nephropathy (n = 12), cystinosis (n = 7), focal and segmental glomerulosclerosis (n = 6), and Schönlein-Henoch disease (n = 5). The quality of life, degree of renal function, and height attainment of the 31 survivors were assessed in June 1985, when their mean age was 22 years (range 14-27), using hospital records and a questionnaire designed to highlight social and psychological problems. Twenty six patients had a functioning transplanted kidney. Average growth during treatment for all survivors was normal, but most were disappointed with their 'final height'. Though five patients had some form of disabling bone disease, all 31 could walk and 27 could run. Sixteen (67%) were in full or part time employment and nine were living independently. A group of 32 patients with juvenile onset diabetes treated at this hospital for at least five years were also asked to complete the questionnaire and of these, 17 responded. On average, their data could usefully be compared with those of cases of end stage renal failure. More of the diabetics had jobs, but most sexually mature patients with renal disease were concerned about their physical appearance and had not achieved any stable long term sexual relationships. We suggest that a poor body image resulting in low self esteem may be responsible for the deficiency and believe that further study in this group is warranted.